Recent trends in chemistry, structure, and various applications of 1-acyl-3-substituted thioureas: a detailed review. Issue 20 (26th April 2022) - Zahra, Urage; Saeed, Aamer; Abdul Fattah, Tanzeela; Flörke, Ulrich; Erben, Mauricio F.
Abstract : This review encapsulates the recently designed acyl thioureas, and their crystal structures, metal complexes and various applications from 2017 to present, including pharmacological aspects, chemosensing and heterogenous catalysis. Abstract : The interest in acyl thioureas has continually been escalating owing to their extensive applications in diverse fields, such as synthetic precursors of new heterocycles, pharmacological and materials science, and technology. These scaffolds exhibit a wide variety of biological activities such as antitumor, enzyme inhibitory, anti-bacterial, anti-fungal, and anti-malarial activities and find utilization as chemosensors, adhesives, flame retardants, thermal stabilizers, antioxidants, polymers and organocatalysts. In addition, the synthesis, and applications of coordination complexes of these ligands have also been overviewed. The current review is a continuation of our previous efforts in this area, focusing on the recent advancements during the period 2017 to present.